Current Therapeutic Innovations in the Treatment of Von Willebrand Disease - Pratiwi, Baiq Bunga Citra; Senna, Cantika Brilliant; Rizki, Mohammad (Jurnal Biologi Tropis, 2025)
Von Willebrand disease (vWD) is the most common hereditary bleeding disorder caused by a deficiency or dysfunction of von Willebrand factor (vWF), a key protein involved in both primary and secondary hemostasis. This study aims to review the current understanding of diagnosis, classification, and management strategies for vWD based on disease type and severity. A literature review approach was employed to analyze recent findings on the pathophysiology, diagnostic criteria, and therapeutic advances related to vWD. Accurate diagnosis remains crucial, as treatment must be tailored to the specific subtype and clinical severity. Current management focuses on increasing circulating levels of vWF and factor VIII through local hemostatic measures, antifibrinolytic agents such as tranexamic acid, desmopressin (DDAVP) for responsive patients, and vWF/factor VIII concentrates for severe cases or DDAVP contraindications. A multidisciplinary perioperative management plan is essential to minimize bleeding risks during surgical or invasive procedures. Despite advances in therapy, challenges persist in early detection and individualized treatment optimization. Comprehensive evaluation, improved clinical awareness, and collaborative care among healthcare providers are vital to enhancing patient outcomes and quality of life.